Gender Representation in Grade Six Science Texttbook of Sri Lanka - Mathura, U.; Piratheeban, K. (Faculty of Education, University of Jaffna, 2024)
The contents of school textbooks serve as a reflection of the prevailing beliefs, values, and practices within a society. The prevalence of gender bias in school textbooks has been identified globally. This portrayal negatively impacts various facets of life; family dynamics, workplace, job interests and educational environments. Therefore, addressing gender bias in our textbooks necessitates a comprehensive approach aimed at creating a society that empowers both genders in all fields equally. This study aims to investigate the disparities present in grade six science textbooks regarding gender representation. Since statistics highlight a persistent gender gap in the field of science, the Grade 6 science textbook was selected for this study using purposive sampling, as students encounter science as a subject for the first time at the junior secondary level. Consequently, gender-related content within textbooks at this stage has the potential to shape their long-term career aspirations and beliefs. Further, visual contents in educational materials can transmit cultural ideologies to learners easily. Therefore, this study was designed as a quantitative analysis, wherein pictures, photos, and images of males and females in the textbook were counted across three themes: visibility, occupational roles, and general activities. The counts were then analyzed using inferential statistical methods specifically chi-square. The results indicate that 75% of the images represent male identity, while only 25% represent females. Hence, the difference in the visibility of genders is not statistically significant (p = 0.199). Additionally, only 33% of female characters show occupational depictions in the textbook, while 67% of images portray male occupational roles. Thus, the difference in the occupational representation of genders is not statistically significant (p = 0.157). Also, male characters are portrayed in heroic and active roles than females. In conclusion, these findings underscore the presence of gender inequality within the textbooks, perpetuating stereotypes and prioritizing male authority and leadership roles. This practice not only perpetuates gender stereotypes but also demotivates the potential for growth and development among women in every field, including the science stream. Therefore, curriculum designers and authors of textbooks should establish a systematic method to present gender equality within the textbooks, ensuring the inclusion of gender-neutral content.
Keywords: Gender in-equality; Gender balance; Gender bias; Gender neutral curriculum